Digitalisasi Pemasaran Produk Ladrang Lele Sebagai Komoditas Unggulan Desa Tambuko, Guluk-Guluk, Sumenep - Maksum (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2023)
ABSTRACT The availability of many springs in Tambuko Village has initiated the community to cultivate catfish. The Tambuko Village community has a Panji Laras Fish farming group consisting of several local communities who cultivate catfish. The Covid-19 pandemic has reduced consumer demand for fresh catfish, resulting in unsold cultivation products. The steps taken by the people of Tambuko Village to deal with this problem are to produce catfish-based snack products. One of the products produced is "Ladrang Lele". The abundance of raw materials as the basis for making this product makes Ladrang Lele production continuous. This Lele Ladrang product is then used as the village's superior product so that it can increase the community's income. This service has the aim of helping the people of Tambuko Village who are mitigating Covid-19 in their economic recovery efforts. This service uses the Participatory Action Research methodology by involving the Tambuko village community who have the ability to produce Village Main Commodities. The steps that will be taken by the servant are conducting Focus Group Discussions (FGD), Entrepreneurship Training and Marketing Digitalization Training. The results obtained during the service activities were Marketing Digitalization carried out by the Tambuko Village community through marketing through the Shopee application including techniques for making attractive product displays, product packaging and strategic promos. The strategy carried out in Digitalizing the Marketing of Lele Ladrang products is to provide an understanding of the importance of entrepreneurship as a basis for product development, marketing training through the shopee application and online marketing assistance to ensure that the Tambuko village community can digitalize marketing, especially the superior village product, namely Ladrang Lele. Keywords: Village Main Products, Marketing Digitalization, Lele Ladrang,